Lifetime Prolonging for Clustered Heterogeneous Wireless Sensor Networks by SEP-FUZZY - Basim Abood; Muhammed Shemyal Nisar; Aliaa Hussien; Yu Li (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The most important consideration in designing protocols for wireless sensor networks is the energy constraint of nodes because in most cases battery recharging is inconvenient or impossible. Therefore, many researches have been done to overcome this demerit. Clustering is one of the main approaches in designing scalable and energy-efficient protocols for WSNs.In this paper, we proposed a novel scheme to investigate the cluster, the Fuzzy Logic Cluster Stable Election Protocol (SEP - FUZZY), which uses Fuzzy Logic Inference System (FIS) in the cluster process. We compare our technique with two approaches (LEACH, and SEP) to show that using a multi parameter FIS enhances the network lifetime significantly. Simulation results demonstrate that the network lifetime achieved by the proposed method could be increased by nearly 27% more than that obtained by LEACH protocol, and by nearly 23% more than that obtained by Stable Election Protocol.